Gender equality measures in tourism: organisational awareness and strategies - Costa, Carlos (2015)
In spite of the high predominance of women working within tourism organisations, numerous factors keep on affecting women’s career advancement and strong inequalities in the workplace persist. Drawing on recent research conducted in Portugal on a nation-wide scale, this study uses quantitative and qualitative analysis to investigate the awareness of gender equality within tourism organisations and the strategies these organisations employ in order to reduce gendered inequalities. An online survey and focus groups were conducted with leaders in the Portuguese tourism industry, in 2013 and 2014. In line with gender ‘invisibility’ theories, results indicate that there is some confusion regarding distinguishing genderbased discrimination at work among tourism leaders. Hence, organisational measures that are believed to endow female employees with more flexibility at work are seen to contribute to the perpetuation of stereotyped gender roles related to domestic and family duties. Furthermore, we find that SMEs, which largely dominate the tourism sector, have particular problems in implementing gender equality measures. Gaining a deeper understanding of the multiple and context-specific truths underlying the available opportunities to men and women in the different levels of the career ladder, is one of this paper’s aims. Policymakers aiming to promote productivity and economic efficiency through increased gender equality at work, can be informed through the findings.